Auditoría en seguridad vial ruta nacional # 25, tramo 2507. pacífico tres unidad funcional 1, abscisas km 21+000 al km 29+999, sector la Virginia – Asia - Ortiz Jajoy, Elkin Dario; Castaño Tobón, Bryan; Suaza Galeano, Maria Elena (Universidad Antonio Nariño, 2021)
The work carried out on Carrying out a Road Safety Audit to the variables: barriers, geometric design of the road and signaling, to establish its condition in front of the road actors that circulate on it, in the section between the abscissa Km 21 + 000 to Km 29 + 999, La Virginia - Asia sector corresponding to national route # 25, section 2507. Pacific, was fulfilled in its entirety and the realization of each of the specific objectives was equal, for this a bibliographic investigation of the works was carried out at the international, national and local level that had as objective the accomplishment of Audits or that were models (manuals) for its realization, as well as a bibliography compilation of the theoretical references to be able to understand the philosophy of the ASV and its roots, it was had into account for the development of the project its methodology which corresponds to the descriptive quantitative, the variables used for each objective were characterized, The methods were presented and the results found were described for with this information, an analysis of the findings was carried out, which found that the road presents good conditions due to the recent construction of only 4 years and the good maintenance that was evidenced in the records in each of the visits made and taking into account the constitutive variables of the route that were audited.